Impacts of contingency factors on the application of strategic management accounting in Vietnamese manufacturing enterprises - Thu Hien Nguyen; Dao Tung Nguyen; Tuan Anh Nguyen; Cong Dinh Nguyen (Cogent Business & Management, 2023)
Based on contingency theory in the study of strategic management accounting, this study examines the internal and external contingencies of the organization that affect the application of strategic management accounting (SMA) in Vietnamese manufacturing enterprises. Using qualitative and quantitative methodology, qualitative methods are used to make questionnaires, and quantitative methods are used to measure the scale and analyze the impact of each factor. The data used in the study was collected using a survey questionnaire from a sample of 395 managers (directors, deputy directors, chief accountants) and accounting staff with knowledge of management accounting/strategic management accounting in Vietnamese manufacturing enterprises. Based on the collected survey data, we performed a multivariable linear regression analysis with SPSS 20 to test the relationship between the contingency factors and the application of SMA. Regression analysis results show that contingencies such as organization size, competitive intensity, organizational structure (decentralized management), organization's technology, business strategy, and perception of market instability positively influence the application of SMA in Vietnamese manufacturing enterprises. Therefore, the study provides insight that contributes to a better understanding of the impact of contingency factors on the application of SMA in the context of manufacturing enterprises in emerging economies like Vietnam. This finding is useful for policymakers and business managers in developing and promulgating mechanisms to influence these random variables to motivate enterprises to use more SMA techniques.
Keywords: M14; M40; M41; 650; enterprise; management accounting (MA); manufacturing enterprises; strategic management accounting (SMA); strategy